2000
DOI: 10.1007/s004290050314
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the pathway of the tensor veli palatini motor nerve during early mouse development

Abstract: The motor axons innervating the tensor veli palatini (TVP) navigate a long distance from the trigeminal motor nucleus to their target. The pathway and time course of the TVP motor nerve during this navigation process remain poorly understood. The aim of this study was to elucidate the peripheral development of the TVP motor nerve, and to confirm when the morphological relationship is established between the nerve and target muscle progenitors. Using immunohistochemistry, carbocyanine fluorescent labeling, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Similarly, Cohen (1993) described that the masticatory compartment emerges and matures earlier than structures associated with the soft-palate field, and that the tensor veli palatini is the earliest of the palatal muscles to appear. In a murine study, Zhang et al (2000) investigated the embryological process by which the mandibular nerve innervates the tensor veli palatini. They suggested that the cells within or supporting the trigeminal ganglion express cues toward which the trigeminal motor axons grow, thereby approaching the target musculature.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Cohen (1993) described that the masticatory compartment emerges and matures earlier than structures associated with the soft-palate field, and that the tensor veli palatini is the earliest of the palatal muscles to appear. In a murine study, Zhang et al (2000) investigated the embryological process by which the mandibular nerve innervates the tensor veli palatini. They suggested that the cells within or supporting the trigeminal ganglion express cues toward which the trigeminal motor axons grow, thereby approaching the target musculature.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in mouse hindbrain, the growing motor neuron axons of the mandibular branch of the trigeminal nerve initially contact the trigeminal sensory ganglion at E9.5 as they exit the hindbrain and coalesce with the sensory axons. Between E9.5 and E10.5, they make contact with the myogenic cells of their target, which surround them throughout the pathfinding process (Zhang et al . 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The size and columnar morphology of the Zfhep-positive Vm matches that observed by DiI-labeling of the trigeminal nerve at the masseter muscle (Widmer et al, 1998), emphasizing that these are differentiated neurons. In the mouse, Vm neurons are born on E9 and E10 (Taber Pierce, 1973), and axon pathfinding of Vm neurons occurs from E9.5 to E13.5 (Zhang et al, 2000), indicating that the Zfhep-positive Vm cells at E13.5 (Fig. 5O) are terminally differentiated.…”
Section: Expression Of Zfhep In the Embryonic Hindbrainmentioning
confidence: 99%